Chemical Modification of Lysozyme, Glucose 6-Phosphate Dehydrogenase, and Bovine Eye Lens Proteins Induced by Peroxyl Radicals: Role of Oxidizable Amino Acid Residues - Lissi-Gervaso, E (2013)
Chemical and structural alterations to lysozyme (LYSO), glucose 6-phosphate dehydrogenase (G6PD), and bovine eye lens proteins (BLP) promoted by peroxyl radicals generated by the thermal decomposition of 2,2?-azobis(2- amidinopropane) hydrochloride (AAPH) under aerobic conditions were investigated. SDS-PAGE analysis of the AAPH-treated proteins revealed the occurrence of protein aggregation, cross-linking, and fragmentation; BLP, which are naturally organized in globular assemblies, were the most affected proteins. Transmission electron microscopy (TEM) analysis of BLP shows the formation of complex protein aggregates after treatment with AAPH. These structural modifications were accompanied by the formation of protein carbonyl groups and protein hydroperoxides. The yield of carbonyls was lower than that for protein hydroperoxide generation and was unrelated to protein fragmentation. The oxidized proteins were also characterized by significant oxidation of Met, Trp, and Tyr (but not other) residues, and low levels of dityrosine. As the dityrosine yield is too low to account for the observed cross-linking, we propose that aggregation is associated with tryptophan oxidation and Trp-derived cross-links. It is also proposed that Trp oxidation products play a fundamental role in nonrandom fragmentation and carbonyl group formation particularly for LYSO and G6PD. These data point to a complex mechanism of peroxyl-radical mediated modification of proteins with monomeric (LYSO), dimeric (G6PD), and multimeric (BLP) structural organization, which not only results in oxidation of protein side chains but also gives rise to radical-mediated protein cross-links and fragmentation, with Trp species being critical intermediates. © 2012 American Chemical Society.